Uplatnění fuzzy modelování v oblasti výzkumu dopadů ekonomických nástrojů internalizace negativních externalit v České republice - Zimmermannová, Jarmila (Univerzita Pardubice, 2012)
The paper focuses on the methodology which was used in the Czech and foreign research papers and studies dealing with the impacts of economic instruments connected with the internalization of negative externalities. Precisely, the main target is to find such studies which are dealing with both the internalization of negative externalities and fuzzy modelling. Firstly, the paper presents different theories regarding the internalization of negative externalities. The second part presents the methodology: the author used the method of scientific database search, particularly in the following databases: Web of Science, Scopus and Google Scholar. The next part is focused on the results of the search. In the Czech Republic, analyses using various qualitative and quantitative methods were found; however, fuzzy modelling has not been used in the internalization of negative externalities yet. Regarding the foreign studies, there are studies dealing with both the internalization of negative externalities and fuzzy modelling. These studies are focused mainly on carbon or energy taxation and also on the CO2 emission trading scheme. Based on these findings, the discussion part of the paper includes also recommendations for the follow-up research.
Application of fuzzy modelling in the research of the impacts of economic instruments connected with the internalization of negative externalities in the Czech Republic
Keywords: internalization of externalities; economic instruments; incidence; literature search; methodology; fuzzy modelling; Czech Republic